Peran Australia dalam Kemerdekaan Indonesia 1942-1945 - Farhan (Program Studi Pendidikan Sejarah Universitas Riau, 2025)
If we look at the role of other countries in helping Indonesia become independent, Australia may not be at the top of the list. Apart from being one of the European countries which also helped England and the Netherlands in carrying out the Dutch Military Aggression I and II, Australia did not feel that helping Indonesia would benefit itself both politically and economically. This reality is inversely proportional to the historical fact that Australia has a 'special' place in the process of achieving victory for the Republic of Indonesia. Many Indonesian workers living in Australia, as well as members of the Labor Party, supported Indonesian independence by going on strike and capturing Dutch ships in port. Apart from that, Australia also encouraged Indonesia's problems to be brought to the United Nations to be heard and resolved diplomatically. So, it would not be wrong if Australia was appointed directly by Indonesia and succeeded in forming the KTN (Three Nation Committee). It can be said that Australia's support is the only European country in the world that supports Indonesian independence. This article will try to look critically at what kind of role Australia gave to the process of Indonesian independence, using historical methods consisting of Heuristics, Verification, Interpretation and Historiography, to be able to see that Australia's influence in the process towards independence cannot simply be juxtaposed in the history of good relations. both countries are still reserved until today.